UCI sports nutrition project: Performance nutrition for sprint and endurance track cycling - Stanley, J.; Leo, P.; Haakonssen, E.; Leckey, J. J. (International Journal of Sport Nutrition and Exercise Metabolism, 2026)
Track cycling is a unique discipline whereby events take place on a velodrome using fixed-gear bicycles. Events cover a spectrum of durations ranging from <11 s through to *60 min. Therefore, diverse and specialized physiological attributes are required to meet the specific demands of competition. Nutrition has a fundamental role in optimizing athlete performance through maintaining overall health, fueling training to develop the required physiological characteristics for success and enabling athletes to meet the energy demands of competition. This review will focus on how nutrition can be optimized to best support the training periodization and competition requirements and provide practical recommendations on fueling strategies for track cycling.